Mapeamento da susceptibilidade a ocorrência de movimentos de massa em Pacoti (Ce) - Silva, Rayssa Magdyelli Nogueira da (2021)
Mapping susceptible areas to mass movements is an important initial step in building knowledge about these phenomenons and, together with other studies, it advises decisions on urban development, risk mitigation and land use management. The mountainous regions are potential scenarios for the occurrence of mass movements, with this, the municipality of Pacoti was chosen, located in the Massif de Baturité, which is a humid enclave in the Ceará state in constant social and economic growth. To assess susceptibility, 8 factors were selected: slope, slope orientation, vertical curvature, horizontal curvature, lithology, lineament density, distance from roads and land use and land cover. The integration of variables was performed in a GIS environment, determining grades for the standardization of values and assigning influence weights to the information planes using the Analytic Hierarchy Process (AHP) method. Two susceptibility maps were generated: the Natural Susceptibility Map to Mass Movements (NSMMM) with the natural variables and the Susceptibility Map to the Mass Movements (SMMM) with the natural and anthropogenic variables. The results indicate the predominance of translational landslides and falls of blocks, mainly in CE-253. Most scars are related to slopes greater than 20%, slopes oriented in the NE and SE quadrants and those characterized as converging-convex. As for geological aspects, there is a strong control of mica schists and migmatites and a lower relationship with the higher densities of lineaments, probably because they occur in places where the humid forest dominates. However, it is clear that scars occur close to at least one lineament. Furthermore, the influence of roads is reinforced, as they favor the occurrence of mass movements in places classified as humid forest and transition forest, the latter being linked to areas previously altered and/or under vegetation recovery. MSNMM demonstrates 55% of the area as high and very high susceptibility, mainly in the central and northern sectors of the municipality. However, the MSMM restricts these classes to 27% of the area, highlighting the roads below 600 meters in altitude, which permeate places with a strong mischaracterization of the natural landscape. Both maps show similarity in the number of scars related to the two classes of greater susceptibility, however, it is noteworthy that the areas of these classes in the MSNMM are about twice as large as the areas in the MSMM, since in the latter the anthropic variables narrow the regions more conducive to mass movements